Process design and optimisation for continuous pharmaceutical manufacturing of atropine and diazepam - Μύτης, Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ), 2018)
Continuous Pharmaceutical Manufacturing (CPM) is a modern industrial paradigm for the production of active pharmaceutical ingredients, providing significant benefits over its batch counterpart, including increased efficiency, cost savings, quality control and safety. The transformation of the pharmaceutical industry requires detailed technoeconomic evaluations. The continuous flow synthesis of atropine and diazepam, two popular drugs with high global sales, has been recently demonstrated. In this work, a CPM flowsheet model is established and optimised for each API, featuring novel kinetic expressions fitted to data, reactor design, separation thermodynamics, mass transfer, liquid-liquid extraction design and costing. Several design variables are calculated by minimising the total cost for a plant with capacity of 100 kg API per annum and a lifetime of 20 years. Different solvents, temperatures and solvent recovery percentage cases are considered. The results are then analysed in order to demonstrate the feasibility of the plants. It was found that the continuous production of atropine is efficient, achieving low operational cost, wastage and E-factors, and yielding high purity. The continuous production of diazepam is not efficient, based on continuous flow chemistry used in this work, as it results in excessive solvent use. There are however promising alternative methods for its continuous production.